Optimization of Somatic Embryogenesis Formation in Hoya (Hoya carnosa (L.) R. Br.) with Different Hormone Combinations - Restanto, Didik Pudji; Prayoga, Mohammad Candra; Jaenuri, Ahmad; Avivi, Sholeh; Soeparjono, Sigit; Selopa, Tanaya Asmara Citra; Ullah, Rehan; Alfarisy, Fariz Kustiawan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Hoya carnosa (L.) R. Br. propagation is conventionally less efficient, and the amount produced is low. This study aims to determine the influence of hormone type and concentration on changes in cell structure and the phase of somatic embryogenesis of the Hoya plant in vitro. The study was conducted in two stages, namely the first stage of callus induction with a combination of BAP (0.4 mg/l, 0.5 mg/l, 0.6 mg/l) and 2,4-D (5 mg/l, 6 mg/l, 7 mg/l) and the second stage of somatic embryogenesis with a combination of BAP hormones (0.5 mg/l, 1.0 mg/l, 1.5 mg/l) and IBA (0.25 mg/l, 0.5 mg/l, and 0.75 mg/l). The data were analyzed using ANOVA and further analyzed by using DMRT. Based on the results, the combination of BAP 0.4 mg/l and 2,4-D 7 mg/l hormones showed the best growth with the parameters of the appearance of callus at 23 days, callus weight 2.92 g, and embryogenic calluses formed with crumb texture and greenish-yellow color. The combination of BAP 1 mg/l and IBA 0.75 mg/l resulted in the frequency of budding emergence of 23.3 days and the number of tendrils 20.7. This treatment was able to produce 5 roots and 2 shoots.